PSYCHOLOGICAL HEALTH OF CHILDREN AS A FACTOR OF SUCCESSFUL EDUCATION (British Journal of Global Ecology and Sustainable Development, 2022)
In the case of impaired development, the child hides his aggressiveness from those around him and becomes emphatically peaceful. Due to the fact that such significant violations are possible at an early age, it is necessary to consider the conditions for optimizing the development of the child.